Transcriptome Analysis Reveals the Inducing Effect of Bacillus siamensis on Disease Resistance in Postharvest Mango Fruit - Zecheng Jiang; Rui Li; Yue Tang; Ziyu Cheng; Minjie Qian; Wen Li; Yuanzhi Shao (Foods, 2022)
Postharvest anthracnose, caused by the fungus Colletotrichum gloeosporioides, is one of the most important postharvest diseases of mangoes worldwide. Bacillus siamensis (B. siamensis), as a biocontrol bacteria, has significant effects on inhibiting disease and improving the quality of fruits and vegetables. In this study, pre-storage application of B. siamensis significantly induced disease resistance and decreased disease index (DI) of stored mango fruit. To investigate the induction mechanisms of B. siamensis, comparative transcriptome analysis of mango fruit samples during the storage were established. In total, 234,808 unique transcripts were assembled and 56,704 differentially expressed genes (DEGs) were identified by comparative transcriptome analysis. Gene ontology (GO) enrichment and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis of DEGs showed that most of the DEGs involved in plant-pathogen interaction, plant hormone signal transduction, and biosynthesis of resistant substances were enriched. Fourteen DEGs related to disease-resistance were validated by qRT-PCR, which well corresponded to the FPKM value obtained from the transcriptome data. These results indicate that B. siamensis treatment may act to induce disease resistance of mango fruit by affecting multiple pathways. These findings not only reveal the transcriptional regulatory mechanisms that govern postharvest disease, but also develop a biological strategy to maintain quality of post-harvest mango fruit.